Gebyar Skrining Kimia Klinik Berbasis POCT sebagai Upaya Deteksi Dini Diabetes Mellitus pada Masyarakat Perkotaan Kelurahan Maleer, Kota Bandung - Ramdhan Gunawan; Wahyu Trimastuti; Edi Suharto; Syaikhul Wahab; Desy Widyaningrum; Mochammad Padhil Zaelani; Milla Anjani (PADMA, 2025)
Diabetes Mellitus is a non-communicable disease with an increasing prevalence, especially in urban areas due to changes in diet, lack of physical activity, and sedentary lifestyles. Early detection through blood glucose testing is crucial to prevent complications such as nephropathy, neuropathy, and cardiovascular disease. Point of Care Testing (POCT) enables rapid, practical, and accurate testing at the community level. This community service activity was carried out in Maleer Village, Batununggal District, Bandung City, involving 30 participants aged 30–65 years. Blood glucose testing was performed using a POCT glucometer, accompanied by education on risk factors, healthy lifestyles, and diabetes mellitus prevention. The results showed that 21 participants (70%) were in the normal category (<140 mg/dL), 6 participants (20%) were prediabetic (140–199 mg/dL), and 3 participants (10%) were ≥200 mg/dL, indicating suspected diabetes mellitus. Overall, 30% of participants had a risk of hyperglycemia and were recommended for further examination at a health facility. POCT-based screening proved to be effective as an early detection strategy and an educational medium to increase public awareness and vigilance regarding the risk of diabetes mellitus.